Frequency control using thermal loads under the proposed ENTSO-E Demand Connection Code - Tindemans,SH; Trovato,V; Strbac,G (IEEE, 2015)
Thermal loads such as refrigerators and electric space heaters use temperature hysteresis controllers that are insensitive to small temperature fluctuations. This results in an ability to modulate their power consumption, thus providing cost-effective frequency support, balancing services and energy arbitrage. In order to partially realise these benefits, ENTSO-E has proposed a mandatory frequency support service for thermal loads in its Network Code on Demand Connection. This is to be implemented as a proportional shift of the setpoint temperature in accordance with frequency deviations. In this paper we argue that this implementation choice results in an unpredictable response that depends strongly on controller details. Furthermore, it restricts the flexibility to implement advanced controllers that deliver multiple services simultaneously. We present a case study that demonstrates very different frequency response patterns from three controllers that are each compatible with the proposed Code. Alternative implementations of the code and controllers are presented to illustrate the scope for improvement.